Al-Qawariri and his experiences in the science of Hadith narrators - Abdel Rahman, Marie (Jordan Journal of Islamic Studies, 2023)
This study presented the sayings of al-Qawariri in al-Jarrah and al-Ta`dil, compared to the sayings of the critics, by extrapolating his statements in the transmitted narrators and his own, both explicit and implicit, and studying them critically in comparison with the sayings of the critics, in order to identify the rank of al-Qawariri among the critics of extremism, leniency, and indulgence. The study included thirty-nine sayings; Of these, eighteen sayings were quoted by critics, and twenty-one sayings of him, and critics agreed in most of his rulings, which felt that he was a moderate, and the study showed his critical position, his rank among critics, and the most important features of his method of criticism.